Essential oils from Mentha viridis (L). L. and Mentha pulegium L.: cytogenotoxic effects on human cells - Silva, Lucilene Fernandes (2017)
The essential oils from Mentha viridis (L). L. and Mentha pulegium L. were studied to assess their inhibitory potential on phospholipase from snake venoms and to determine their cytogenotoxic action on human cells. These essential oils were able to inhibit the breakdown of phospholipids induced by venoms of snakes of the Bothrops genus. Both oils presented hemolytic activity, although the Mentha viridis (L). L. oil induced hemolysis only at the highest concentrations (14.6 and 29 µL∙mL−1 ). The essential oil from M. viridis induced 3.9; 8.6 and 16.2 times greater damage to human leukocyte DNA than that observed with the positive control (100 µg∙µL−1 doxorubicin) at concentrations of 0.25; 0.5 and 1.0 µL∙mL−1 , respectively. A similar effect was observed for the oil from M. pulegium (2.1, 2.5 and 15.8 times greater damage). The results extend the characterization of these essential oils and demonstrate their potential use in industries.